A formação em Química discutida com base nos modelos proposto por estudantes de pós-graduação para o fenômeno de dissolução - Souza, Karina Aparecida de Freitas Dias de [UNESP]; Cardoso, Arnaldo Alves [UNESP] (Sociedade Brasileira de Química, 2009)
Mental models play an important role in the evolution of an individual's so-called knowledge. Using such representations, students can explain, foresee, and attribute causality to observed phenomena. In the case of Chemistry, the ability to work mentally with models assumes great importance, due to the microscopic component that is characteristic of this science. With the objective of exploring students' ability to work with models, 27 students of the Chemistry Institute of UNESP were asked to describe the mechanisms of dissolution, in water, of NaCl, HCl and HCN, as well as the partial dissolution of I2. Due to difficulties of access to complex descriptors of these processes, each student was asked to explain the phenomena using words and drawings. The results of these investigations were analyzed, and enabled construction of a framework representing the Chemistry students' theoretical training, especially with respect to their most important transferred skill: an ability to model the physical world.
Graduation in chemistry discussed in relation to graduate students' models concerning the phenomenon of dissolution
Keywords: mental models; dissolution in water; Chemistry education